Effects of extrusion parameters on properties of 3D printing concrete with coarse aggregates. (28th March 2022) - Ji, Guangchao; Xiao, Jianzhuang; Zhi, Peng; Wu, Yu-Ching; Han, Nv
Highlights: The influence of different nozzle directions on the properties of 3DPC is studied. The macro and micro properties of 3DPC with different scrapers are quantified. A DEM model and automatic scraper system are designed for future work. Abstract: Different extrusion systems have been widely used in previous studies, researches on the influence of nozzle directions and scrapers on properties of 3D printing concrete (3DPC) were however very limited. Therefore, the buildability, mechanical properties, and microstructure of concrete printed by different nozzle directions and scrapers were studied in this investigation. It has been found that the vertical extrusion force would reduce buildability, whereas increase the mechanical properties of 3DPC. Microstructure indicates that the interlayer porosity of concrete printed by vertical nozzle is 79.8% of that printed by horizontal nozzle. Besides, compared with the vertical nozzle without scraper (VN), the vertical nozzle with 40 mm-height scrapers (VN-40S) could reduce the vertical deformation of 3DPC by 20%−25% and increase the flexural strength parallel to the printing direction of 3DPC by 44%–49%. The interlayer porosity of concrete printed by VN-40S is 70.1% of that printed by VN. Longer scrapers could influence more printed layer fresh concrete, so the porosity is further reduced. Finally, a discrete element method (DEM) and automatic scraper system are discussed for the future work of 3DPC.